2009
DOI: 10.1074/jbc.m806267200
|View full text |Cite
|
Sign up to set email alerts
|

The Serine Protease Marapsin Is Expressed in Stratified Squamous Epithelia and Is Up-regulated in the Hyperproliferative Epidermis of Psoriasis and Regenerating Wounds

Abstract: The trypsin-like serine protease marapsin is a member of the large protease gene cluster at human chromosome 16p13.3, which also contains the structurally related proteases testisin, tryptase ⑀, tryptase ␥, and EOS. To gain insight into the biological functions of marapsin, we undertook a detailed gene expression analysis. It showed that marapsin expression was restricted to tissues containing stratified squamous epithelia and was absent or only weakly expressed in all other tissues, including the pancreas. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…Mouse marapsin expressed in mammalian cells is membraneassociated but shed by phosphatidylinositol-specific phospholipase C (3), suggesting that the transmembrane peptide is swapped for a GPI anchor (12). In agreement with hydropathy analysis as well as with predictions that the human enzyme lacks a C-terminal anchor, native human marapsin is secreted from an esophageal cell line (13). The marapsin gene is expressed by a variety of human, mouse, and opossum tissues (9,10,12,13).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Mouse marapsin expressed in mammalian cells is membraneassociated but shed by phosphatidylinositol-specific phospholipase C (3), suggesting that the transmembrane peptide is swapped for a GPI anchor (12). In agreement with hydropathy analysis as well as with predictions that the human enzyme lacks a C-terminal anchor, native human marapsin is secreted from an esophageal cell line (13). The marapsin gene is expressed by a variety of human, mouse, and opossum tissues (9,10,12,13).…”
supporting
confidence: 52%
“…In agreement with hydropathy analysis as well as with predictions that the human enzyme lacks a C-terminal anchor, native human marapsin is secreted from an esophageal cell line (13). The marapsin gene is expressed by a variety of human, mouse, and opossum tissues (9,10,12,13). In humans and mice, it is especially abundant in stratified squamous epithelia of cornea, larynx, esophagus, and cervix (13,14) and is induced in wounded and psoriatic skin (13,14).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…In contrast to major effects on the innate immune response by keratinocytes in a proinflammatory context, IL-22 and TNF-α did not synergize in the enhanced wound healing clearly induced by Th22 cells. This effect was only IL-22 dependent and reflected the induction of promigratory genes in keratinocytes by IL-22 (8,14,44,45). These data indicate a double function of IL-22 in cutaneous immunity: on the one hand, being protective and regenerative, and on the other hand, amplifying TNF-α-induced signals to contribute to a proinflammatory microenvironment during skin immune reactions.…”
Section: Figurementioning
confidence: 80%
“…Validation of these results by quantitative reverse transcription PCR (qRT-PCR) revealed that Klk6 (22,23) and marapsin (also known as Prss27) (24) mRNAs were expressed at 10-fold higher levels in the skin from Jak1…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 97%